Mitigasi Literasi Digital Berbasis Microblogging: Studi Etnografi dalam Pengembangan Keterampilan Menulis Siswa SMA - Al Hamidi, Muhammad Fauzi; Masud, Masud; Ambarwati, Ari; Wahyuni, Sri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the role of microblogging platforms such as Twitter (X) and Threads as digital literacy tools to enhance the writing skills of high school students within the Merdeka Belajar (Freedom to Learn) Program. The background of this research stems from the high usage of social media among Indonesian adolescents (89% according to APJII, 2023), which remains underutilized for educational purposes. Using a digital ethnography approach, the study analyzed the activities of 30 students over 4-6 months through microblog content observation (150+ posts), in-depth interviews, and document analysis. The results indicate that interactive features of microblogging platforms, such as real-time feedback, significantly boosted students' writing motivation (85% of respondents) and improved writing quality, including enhanced diction precision (45%) and inter-sentence cohesion (32%). However, challenges such as distractions (45% of students), platform misuse (25%), and disparities in digital literacy among skill groups were also identified. These findings underscore the potential of microblogging as an effective pedagogical tool, provided it is supported by structured strategies, teacher training, and digital risk mitigation. This study offers practical recommendations for educators to integrate microblogging into curricula while addressing gaps in the literature on social media-based digital literacy in the Indonesian context.